Management of Carpal Tunnel Syndrome: Surgical vs Conservative approach - Grunwald, Katarzyna; Dawidowicz, Marcel; Aleksandrowicz, Hanna; Kalinowska, Zuzanna; Karska, Karolina; Sokołowska, Julia (Journal of Education, Health and Sport, 2026)
Introduction and Purpose: Carpal Tunnel Syndrome (CTS) is the most common peripheral neuropathy, causing significant functional impairment and socioeconomic burden. Relative effectiveness of conservative versus surgical interventions remains debated due to heterogeneity in study designs. This study aims to systematically review randomized controlled trials (RCTs) published from 2009 onwards to evaluate the comparative efficacy and durability of these treatment strategies in adult patients. Material and Method: A systematic search was performed in PubMed, Scopus, Web of Science, and the Cochrane Library for RCTs published between 2009 and 2022. The review included adults with clinically or electrophysiologically confirmed CTS. Analyzed interventions included conservative treatments, such as splinting, corticosteroid injections, perineural dextrose, platelet-rich plasma (PRP), manual therapy and surgical release techniques. Primary outcomes extracted included symptom severity and functional status (BCTQ), pain intensity, and neurophysiological parameters. Results: Conservative therapies, particularly corticosteroids and manual therapy, demonstrate significant short-term (1–3 months) symptom relief often comparable to surgery. Perineural dextrose and PRP show superior mid-term efficacy compared to steroids. Surgical decompression provides superior long-term durability (>6 months) with significantly lower recurrence rates and a reduced need for subsequent interventions. Conclusions: Conservative management serves as an effective first-line option for mild-to-moderate CTS, providing fast relief. Emerging regenerative injections offer better durability than traditional steroids. Nevertheless, surgical release remains the definitive treatment for ensuring long-term remission, particularly in severe cases. Therapy should be individualized, prioritizing non-invasive methods initially while reserving surgery for lasting anatomical correction.